Medan Nature School with the Application of Energy Saving Ecological Architecture - Devin Defriza Harisdani; Samantha Theresia (International Journal of Architecture and Urbanism, 2020)
Schools in Indonesia are conventional schools where students and teachers do activities which are commonly referred to as teaching and learning activities even though the school is not a place to lure students with stacks of information but also to train in terms of maturity of thinking and maturity of attitude. Now has developed a nature school that uses nature as a learning space, media, and teaching materials and learning objects that can take advantage of nature and can preserve nature for the next life. However, Medan only has a few nature schools. This nature school design uses the problem-solving methodology approach to solve existing problems, starting from the formulation stage, data collection, analysis to synthesis using survey techniques, interviews, literature studies, and comparative studies. So, through the design of Medan Nature School is expected to be able to educate students who emphasize education, character, and skills with the Ecological Architecture design approach where school buildings can maintain the environment to be sustainable, related to the plantation system, animal husbandry system, utility system, circulation systems, building design, and layout.